2013
DOI: 10.1017/s0967199413000130
|View full text |Cite
|
Sign up to set email alerts
|

Moments of induced spawning and embryonic development of Brycon amazonicus (Teleostei, Characidae)

Abstract: Based on the economic and ecological relevance of Brycon amazonicus, the goal of this work was to describe the diameter of oocytes and eggs of this species, as well as the chronological embryonic development. The material was provided by Buriti fish farm, Nova Mutum - MT, Brazil. Samples of both oocytes and eggs were obtained from extrusion to hatching. The material was fixed and measured under stereomicroscope, and the samples were divided for light microscopy or scanning electron microscopy (SEM) analyses. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
9
0
3
Order By: Relevance
“…The morphological and morphometric characteristics of dry fertilized eggs and hydrated eggs were similar to those reported in other studies using Brycon (Bernardino et al, 1993;Lopes et al, 1995;Romagosa et al, 2001; Clavijo-Ayala and Arias Castellanos 2004; Nakaghi et al, 2013). The matrinxã's pattern of development is similar to that reported by Kimmel et al (1995) for zebra fish, in which the blastoderm is formed by a single outer layer of flattened cells, known as the involucral outer layer, and a more rounded deep layer of cells.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The morphological and morphometric characteristics of dry fertilized eggs and hydrated eggs were similar to those reported in other studies using Brycon (Bernardino et al, 1993;Lopes et al, 1995;Romagosa et al, 2001; Clavijo-Ayala and Arias Castellanos 2004; Nakaghi et al, 2013). The matrinxã's pattern of development is similar to that reported by Kimmel et al (1995) for zebra fish, in which the blastoderm is formed by a single outer layer of flattened cells, known as the involucral outer layer, and a more rounded deep layer of cells.…”
Section: Discussionsupporting
confidence: 87%
“…Epiboly starts with the deep layer cells radially intercalating and the yolk cell "doming," which was recorded by Andrade-Talmelli et al (2001) and Paes (2008) when eggs presented with 30% epiboly and by Kimmel et al (1995) and Sampaio (2006) when it was in the 50% epiboly stage. With B. amazonicus, Clavijo-Ayala and Arias Castellanos (2004) observed the early gastrula (10% epiboly) at 5 h AF (27.5 ± 0.2 °C), and Nakaghi et al (2013) observed the beginning of the epiboly and gastrula stage when cell proliferation covered approximately 30% of the yolk, at 3 h AF (28.08 °C). We observed the same event 1 h 20 min AF (29.9 ± 0.18 °C), and the difference could be related to temperature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The sequence of events observed during embryogenesis of B. gouldingi was similar to that reported for other species of Brycon , such as piabanha Brycon insignis Steindachner 1877 (Andrade‐Talmelli et al ., ), B. cephalus (Lopes et al ., ; Romagosa et al ., ), B. orbignyanus (Reynalte‐Tataje et al ., ), jatuarana Brycon amazonicus (Spix & Agassis 1829) (Nakaghi et al ., ) and other teleosteans such as hybrids of P. corruscans × P. fasciatum (Faustino et al ., ) and P. lineatus (Ninhaus‐Silveira et al ., ). In general, the basic developmental mechanisms of teleosteans are similar and only differ in the chronology of events (Falk‐Petersen, ).…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, antioxidant defense capacity against ammonia stress (Pan et al, 2011), the early development of skull (Vandewalle et al, 2005), embryo development (Nakaghi et al, 2013;Weber et al, 2012), etc. have been studied.…”
mentioning
confidence: 99%